A Digital Cognitive Aid for Anesthesia to Support Intraoperative Crisis Management: Results of the User-Centered Design Process - Schild, Stefanie; Sedlmayr, Brita; Schumacher, Ann-Kathrin; Sedlmayr, Martin; Prokosch, Hans-Ulrich; St. Pierre, Michael (JMIR mHealth and uHealth, 2019)
Background: Stressful situations during intraoperative emergencies have negative impact on human cognitive functions. Consequently, task performance may decrease and patient safety may be compromised. Cognitive aids can counteract these effects and support anesthesiologists in their crisis management. The Professional Association of German Anesthesiologists set up a project to develop a comprehensive set of digital cognitive aids for intraoperative emergencies. A parallel development for several software platforms and stationary and mobile devices will accommodate the inhomogeneity of the information technology infrastructure within German anesthesia departments.
CRIS-Team WoS Importer:2019-05-24

Alpha-1-antitrypsin-deficiency is associated with lower cardiovascular risk: an approach based on federated learning - Zöller, Daniela; Haverkamp, Christian; Makoudjou, Adeline; Sofack, Ghislain; Kiefer, Saskia; Gebele, Denis; Pfaffenlehner, Michelle; Boeker, Martin; Binder, Harald; Karki, Kapil; Seidemann, Christian; Schmeck, Bernd; et al. (Respiratory Research, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is an inflammatory multisystemic disease caused by environmental exposures and/or genetic factors. Inherited alpha-1-antitrypsin deficiency (AATD) is one of the best recognized genetic factors increasing the risk for an early onset COPD with emphysema. The aim of this study was to gain a better understanding of the associations between comorbidities and specific biomarkers in COPD patients with and without AATD to enable future investigations aimed, for example, at identifying risk factors or improving care. Methods: We focused on cardiovascular comorbidities, blood high sensitivity troponin (hs-troponin) and lipid profiles in COPD patients with and without AATD. We used clinical data from six German University Medical Centres of the MIRACUM (Medical Informatics Initiative in Research and Medicine) consortium. The codes for the international classification of diseases (ICD) were used for COPD as a main diagnosis and for comorbidities and blood laboratory data were obtained. Data analyses were based on the DataSHIELD framework. Results: Out of 112,852 visits complete information was available for 43,057 COPD patients. According to our findings, 746 patients with AATD (1.73%) showed significantly lower total blood cholesterol levels and less cardiovascular comorbidities than non-AATD COPD patients. Moreover, after adjusting for the confounder factors, such as age, gender, and nicotine abuse, we confirmed that hs-troponin is a suitable predictor of overall mortality in COPD patients. The comorbidities associated with AATD in the current study differ from other studies, which may reflect geographic and population-based differences as well as the heterogeneous characteristics of AATD. Conclusion: The concept of MIRACUM is suitable for the analysis of a large healthcare database. This study provided evidence that COPD patients with AATD have a lower cardiovascular risk and revealed that hs-troponin is a predictor for hospital mortality in individuals with COPD.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Alpha-1-antitrypsin deficiency; Cardiovascular; Cholesterol; COPD; Troponin

Cognitive aids for crisis management in anaesthesiology. Principles and applications - Eismann, H.; Schild, Stefanie; Neuhaus, C.; Baus, J.; Happel, O.; Heller, A. R.; Richter, T.; Weinert, M.; Sedlmayr, B.; Sedlmayr, M.; St. Pierre, Michael (Anästhesiologie & Intensivmedizin, 2020)
Anaesthesiology has witnessed a growing acknowledgement of the fact that stress can have a negative impact on individual cognitive function and effective team performance. Cognitive aids such as checklists have come to be viewed as promising tools in the management of critical events. While checklists have been an integral part of the safety strategy in aviation for many decades, there has been little progress in establishing related concepts in anaesthesiology. Reasons for this reluctance are the lack of usability of the cognitive aids developed and the fact that these cognitive artefacts do not support established treatment processes. The main reason, however, are the different system properties of technical devices and biological systems. While it is possible to define the one best way of solving a technical problem and translate this knowledge into a linear checklist, the behaviour of biological systems is dynamic and adaptive, which makes it impossible to predict with certainty the cause of a pathophysiological disturbance and define the single best way to solve a problem. Rather than being restricted to a linear checklist, cognitive aids can improve emergency management by helping experienced teams to remember and excel. The German Cognitive Aid Working Group of the Professional Association of German Anaesthesiologists (BDA) and the German Society of Anaesthesiology and Intensive Care Medicine (DGAI) has developed a digital cognitive aid for intraoperative emergencies in an iterative user-centred design process. the future challenge will be to understand the physical, cognitive and social aspects of implementing the cognitive aid into established processes of crisis management in anaesthesia.
CRIS-Team WoS Importer:2020-07-03

Data Model Requirements for a Digital Cognitive Aid for Anesthesia to Support Intraoperative Crisis Management - Schild, Stefanie; Gründner, Julian; Gulden, Christian; Prokosch, Hans-Ulrich; St. Pierre, Michael; Sedlmayr, Martin (Applied Clinical Informatics, 2020)
OBJECTIVE: The aim of this study is to define data model requirements supporting the development of a digital cognitive aid (CA) for intraoperative crisis management in anesthesia, including medical emergency text modules (text elements) and branches or loops within emergency instructions (control structures) as well as their properties, data types, and value ranges. METHODS: The analysis process comprised three steps: reviewing the structure of paper-based CAs to identify common text elements and control structures, identifying requirements derived from content, design, and purpose of a digital CA, and validating requirements by loading exemplary emergency checklist data into the resulting prototype data model. RESULTS: The analysis of paper-based CAs identified 19 general text elements and two control structures. Aggregating these elements and analyzing the content, design and purpose of a digital CA revealed 20 relevant data model requirements. These included checklist tags to enable different search options, structured checklist action steps (items) in groups and subgroups, and additional information on each item. Checklist and Item were identified as two main classes of the prototype data model. A data object built according to this model was successfully integrated into a digital CA prototype. CONCLUSION: To enable consistent design and interactivity with the content, presentation of critical medical information in a digital CA for crisis management requires a uniform structure. So far it has not been investigated which requirements need to be met by a data model for this purpose. The results of this study define the requirements and structure that enable the presentation of critical medical information. Further research is needed to develop a comprehensive data model for a digital CA for crisis management in anesthesia, including supplementation of requirements resulting from simulation studies and feasibility analyses regarding existing data models. This model may also be a useful template for developing data models for CAs in other medical domains.
CRIS-Team Scopus Importer:2020-03-27

Detection of Paroxysmal Atrial Fibrillation: A Computationally Efficient Algorithm for Use in a Wearable Telemedical System - Kirchner, Jens; Schild, Stefanie; Fischer, Georg (2017 IEEE International Sympium on Medical Measurements and Applications (MeMeA), 2017)
For early detection of the sporadic events of paroxysmal atrial fibrillation (AF), long-term ECG monitoring and data evaluation are required. To allow energy-efficient on-device preprocessing of the data, an as simple as possible algorithm is sought. The proposed approach is based on heart frequency data only and makes use of the increased heart rate variation with the occurrence of AF. Criteria for the choice of the free parameters of this method are derived, and it is shown that, under these conditions, results are insensitive against variations of these parameters. If a compromise between sensitivity and specificity is sought, i.e. equality of these values, 89.4% are obtained in average. If instead sensitivity alone is optimized, i. e. for use with additional AF detection strategies, an average value of 99.6% is reached with specificity 38.4%. The algorithm forms the first step in the development of a computationally and thus energy efficient signal processing module for the purpose of reducing the amount of data that has to be stored or transmitted and then evaluated by the treating physicia
Keywords: paroxysmal atrial fibrillation detection; wearable telemedical system; sporadic event detection; long-term ECG monitoring; energy-efficient on-device data preprocessing; heart frequency data; atrial fibrillation detection strategy; energy efficient signal processing; Sensitivity; Heart rate; Electrocardiography; Optimization; Medical services; Paroxysmal Atrial Fibrillation; Electrocardiogram; Heart Rate Variability; Cardiac Diseases; Diagnostic Monitoring

DQAgui: a graphical user interface for the MIRACUM data quality assessment tool - Mang, Jonathan M.; Seuchter, Susanne A.; Gulden, Christian; Schild, Stefanie; Kraska, Detlef; Prokosch, Hans-Ulrich; Kapsner, Lorenz (BMC Medical Informatics and Decision Making, 2022)
Background: With the growing impact of observational research studies, there is also a growing focus on data quality (DQ). As opposed to experimental study designs, observational research studies are performed using data mostly collected in a non-research context (secondary use). Depending on the number of data elements to be analyzed, DQ reports of data stored within research networks can grow very large. They might be cumbersome to read and important information could be overseen quickly. To address this issue, a DQ assessment (DQA) tool with a graphical user interface (GUI) was developed and provided as a web application. Methods: The aim was to provide an easy-to-use interface for users without prior programming knowledge to carry out DQ checks and to present the results in a clearly structured way. This interface serves as a starting point for a more detailed investigation of possible DQ irregularities. A user-centered development process ensured the practical feasibility of the interactive GUI. The interface was implemented in the R programming language and aligned to Kahn et al.’s DQ categories conformance, completeness and plausibility. Results: With DQAgui, an R package with a web-app frontend for DQ assessment was developed. The GUI allows users to perform DQ analyses of tabular data sets and to systematically evaluate the results. During the development of the GUI, additional features were implemented, such as analyzing a subset of the data by defining time periods and restricting the analyses to certain data elements. Conclusions: As part of the MIRACUM project, DQAgui is now being used at ten German university hospitals for DQ assessment and to provide a central overview of the availability of important data elements in a datamap over 2 years. Future development efforts should focus on design optimization and include a usability evaluation.
CRIS-Team Scopus Importer:2022-08-26
Keywords: Data accuracy; Data quality assessment (DQA); Documentation; Electronic health records (EHR); Feasibility studies; Mobile applications; User–computer interface

Eosinopenia as Predictor of Disease Severity in Patients With Community-Acquired Pneumonia: An Observational Study - Weckler, Barbara Christine; Pott, Hendrik; Race, Alan; Jugkaeo, Nattika; Karki, Kapil; Ringshandl, Stephan; Seidemann, Christian; Schöndorf, Ines; Renz, Harald; Fähndrich, Sebastian; Jung, Anna Lena; Bertrams, Wilhelm; et al. (Chest, 2024)
CRIS-Team Scopus Importer:2024-10-25

Evaluation of a Patient-Facing Digital Prototype for Perioperative Risk Assessment. - Mang, Jonathan; Schild, Stefanie; Prokosch, Hans-Ulrich; Jeleazcov, Christian; Heinrich, Anne; Toddenroth, Dennis (Studies in health technology and informatics, 2019)
Preparations for anesthesiological management of patients build on preoperative patient self-reports concerning risk factors and comorbidities. In this setting, electronic documentation could facilitate innovative computerized functions, although patient-facing digital questionnaires require appropriate tools that patients can access effectively. To explore the feasibility of an electronic application for preoperative data acquisition directly from patients, a digital, tablet-based prototypical application has been developed within a user-centered design process in order to replace a previously used paper-based anamnesis sheet for perioperative risk evaluation. The implemented prototype has been extensively tested and iteratively improved to progressively provide an easy-to-use data entry function. To assess the suitability of this tool for everyday data acquisition by patients and physicians and to identify usability problems, the stepwise development process was accompanied by a heuristic evaluation as well as a think-aloud evaluation, while another 56 participating patients completed a feedback sheet according to ISO 9241/10. The latter method detected additional usability problems that occurred during the use of the application, which contributed to iterative improvements of the prototype. Throughout the development process, 81 issues were identified and largely resolved. After these revisions of the prototype, the number of problems found per tester decreased from 4.75 to 0.96, while the overall rating increased to 6.14 out of 7 points (SD = 1.2). These improvements demonstrate the value and efficiency of such a user-centered design process and illustrate that a user-friendly patient-facing digital data entry can replace preoperative paper questionnaires for anesthesiological management.
EVALuna2:209490

Evaluation of a patient-facing digital prototype for perioperative risk assessment - Mang, Jonathan; Schild, Stefanie; Prokosch, Hans-Ulrich; Jeleazcov, Christian; Heinrich, Anne; Toddenroth, Dennis (ICT for Health Science Research - Proceedings of the EFMI 2019 Special Topic Conference, 2019)
Preparations for anesthesiological management of patients build on preoperative patient self-reports concerning risk factors and comorbidities. In this setting, electronic documentation could facilitate innovative computerized functions, although patient-facing digital questionnaires require appropriate tools that patients can access effectively. To explore the feasibility of an electronic application for preoperative data acquisition directly from patients, a digital, tablet-based prototypical application has been developed within a user-centered design process in order to replace a previously used paper-based anamnesis sheet for perioperative risk evaluation. The implemented prototype has been extensively tested and iteratively improved to progressively provide an easy-to-use data entry function. To assess the suitability of this tool for everyday data acquisition by patients and physicians and to identify usability problems, the stepwise development process was accompanied by a heuristic evaluation as well as a think-aloud evaluation, while another 56 participating patients completed a feedback sheet according to ISO 9241/10. The latter method detected additional usability problems that occurred during the use of the application, which contributed to iterative improvements of the prototype. Throughout the development process, 81 issues were identified and largely resolved. After these revisions of the prototype, the number of problems found per tester decreased from 4.75 to 0.96, while the overall rating increased to 6.14 out of 7 points (SD = 1.2). These improvements demonstrate the value and efficiency of such a user-centered design process and illustrate that a user-friendly patient-facing digital data entry can replace preoperative paper questionnaires for anesthesiological management.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Anesthesiologic patient history; Digital questionnaire; ISO 9241; Usability evaluation

Funktionalität und Bedienung von eGENA, der elektronischen Gedächtnis- und Entscheidungshilfe für Notfälle in der Anästhesiologie - Neuhaus, C.; Schild, Stefanie; Eismann, H.; Baus, J.; Happel, O.; Heller, A. R.; Richter, T.; Weinert, M.; Sedlmayr, B.; Sedlmayr, M.; Prokosch, Hans-Ulrich; Schleppers, A.; et al. (Anästhesiologie & Intensivmedizin, 2020)
The German Cognitive Aid Working Group of the Professional Association of German Anaesthesiologists (BDA) and the German Society of Anaesthesiology and Intensive Care Medicine (DGAI) developed 'eGENA', a digital cognitive aid for intra- and postoperative emergencies using an iterative user-centred design process according to DIN EN ISO 9241-210. The digital cognitive aid is the first application for crisis management in anaesthesiology where detailed documentation of the development process was published. eGENA is a progressive web application (PWA) which stores information offline on stationary and mobile devices. The user can access information by first choosing a patient group (infant, adult, parturient) and then one of the following search options: 'resuscitation', 'alphabetical search', 'ABCDE approach', and 'body navigator'. The information accessed is further tailored to the patient's clinical status: 'awake' vs. 'anaesthetised', and 'haemodynamically stable' vs. 'haemodynamically unstable'. Information is not presented as one single continuous text, but rather subdivided into the tabs 'immediate action', 'diagnosis, and 'therapy'. Information not pertaining to the linear sequence of action is presented under 'symptoms' and 'differential diagnosis'. eGENA comprises more than 50 emergencies including those listed in the Helsinki Declaration on Patient Safety in Anaesthesiology for which institutions should have protocols. In addition, eGENA supports non-technical skills by providing impulses for decision-making, teamwork and resource management. Users can customise eGENA by editing locally relevant information and share the revised content. eGENA can be downloaded for free from the website of the Professional Association of German Anaesthesiologists and the German Society of Anaesthesiology and Intensive Care Medicine together with training material supporting the implementation.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Cognitive Aid; Crisis Management; Decision-making; Memory; Web Application